The European Union Education Policy in the labyrinth of the Minotaur - Javier Manuel Valle López (FahrenHouse, 2010)
This article is a review to the current status of the European Union educational policy, analyzing the strategic framework for cooperation in education for 2020 (so called ET 2020) in the context of the historical background of that policy. For the author, the Treaty of Lisbon (2009). For the author, the Treaty of Lisbon (2009) has not led Europe to a sufficient clarification of its future policy as a supranational entity.  That has also consequences in its policy of education. Those consequences allow to the author the original license to make a parallel between the current situation of the education policy of the European Union and the classical myth of the Minotaur of Crete.